Legal basis for the protection of trade secrets in the implementation of an electronic transaction - Zhumadilova, M.A.; Issaeva, A.Zh.; Aitimov, B.Zh. (Bulletin of the Karaganda University “Law Series”, 2022)
The purpose of the study is to consider legal relations in the implementation of an electronic transaction and to develop proposals in the field of trade secret protection. The security of trade secrets in the implementation of an electronic transaction is relevant in the field of information security. Most measures to protect confiden-tial information and its technical measures themselves in many cases are u nattainable. As research methods the dialectical method, the method of analysis and comparative-legal analysis were used. In particular, in the study of the development of Kazakhstan's legislation on electronic transactions dialectical method was used; the analysis method was used to assess the obtained achievements in the legal protection of trade secrets in the implementation of an electronic transaction, identifying problems and shortcomings in it. At the same time, the method of comparative-legal analysis has been applied in order to determine the degree of protec-tion of commercial secrets in the implementation of an abroad electronic transaction. In the course of the study, the following results were achieved: a) it is studied that the protection of trade secrets in the implemen-tation of an electronic transaction is considered for the first time in domestic legal science as an object of scientific research; b) the relevance of the protection of trade secrets in the implementation of an electronic transaction and the problems of its legal support are revealed. In conclusion, the scientific article substantiates the need for the adoption of the law "On Trade Secrets" with justification of possible consequences in case of failure to ensure the protection of trade secrets.